Intensified Late Miocene Deformation in the Northern Qaidam Basin, Northern Tibetan Plateau, Constrained by Apatite Fission-Track Thermochronology - He, Pengju; Song, Chunhui; Wang, Yadong; Zhang, Yihu; Chen, Wenqi; Meng, Qingquan; Zhao, Yuanhao (Frontiers in Earth Science, 2021)
The Cenozoic tectonic evolution of the North Qaidam-Qilian Shan fold-thrust belt in the northern Tibetan Plateau is important to understanding the tectonic rejuvenation of orogeny and growth of the plateau. However, the deformation processes in this region remain controversial. This study presents new apatite fission track (AFT) data from Paleogene strata in the northern Qaidam Basin to investigate the time of deformation in this site. Thermal modeling of these partially annealed detrital AFT ages shows a thermal history with a noticeable transition from heating to cooling after ∼10 Ma. This transition is attributed to the intensified thrusting and folding of the northern Qaidam Basin since ∼10 Ma. Integrated with published tectonics and thermochronology results, we suggest the North Qaidam-Qilian Shan fold-thrust belt experienced prevailing tectonism since the late Miocene.